Constraints in adoption of smart agricultural practices - ROHILA, ANIL KUMAR; KUMAR, AJAY; MUKTESHAWAR, RATI; GHANGHAS, BHARAT SINGH; KAVITA, KAVITA; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2021)
It is globally accepted that adoption of smart agricultural practices (SAPs) are only alternate to feed the continuous increasing population of the world. The purpose of this study was to identify the constraints faced by farmers in adoption of smart agricultural practices in Haryana. Study was carried out (2017) in Hisar and Kaithal districts of Haryana state of India. Data were collected with the help of well-structured and pre-tested questionnaire. A sample of 180 respondents were explored in personal interviews using a three-point continuum scale for the constraints i.e. very serious, serious and not so serious and scores were given as 3, 2 and 1, respectively. Data were analysed using Statistical Package for the Social Sciences (SPSS). Present study concluded that major constraints for SAPs were lack of seeds of new high yielding varieties with weighted mean score (WMS) 2.36, lack of knowledge for seed treatment (2.36), lack of farm equipment (2.30), inadequate information (2.92), inadequate knowledge and (2.92), scarcity of canal water (2.61), lack of minimum support price (2.73), all crops not covered under crop insurance (2.69), and nonavailability of good animal breed (2.19). Moreover, 11 independent variables included in the study jointly contributed 44% variation in the constraints of the respondents regarding in adoption of SAPs.